2019
DOI: 10.1007/s10865-019-00010-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and demographic factors associated with fatigue and social adjustment in young people with severe chronic fatigue syndrome/myalgic encephalomyelitis: a preliminary mixed-methods study

Abstract: This mixed-methods study investigated factors associated with fatigue, disability and school attendance in young people with severe CFS/ME. Participants' illness experiences were also explored. Questionnaires were completed at baseline (T1) and approximately 5 months later (T2). There were 51 participants aged between 12 and 25, with a mean age of 18.8 years (SD 3.4). At T1, participants reported severe fatigue and poor social adjustment. Stronger fear avoidance beliefs at T1 were associated with higher fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
1
7
0
1
Order By: Relevance
“…Unlike previous studies [6,31,62,66], we did not find higher rates of depression in adolescents with ME/CFS compared with healthy controls, nor an increase in depression over time. However, our findings do support two recent paediatric ME/CFS follow-up studies showing stable depression levels over time [67,68]. Although Loades et al [68] observed consistently higher levels of depression in the paediatric ME/CFS group than healthy controls, baseline ME/CFS depression was found to explain most of the variance in follow-up ME/CFS depression, which appears to suggest stable depression levels across time in paediatric ME/CFS.…”
Section: Trajectories Of Health and Psychological Wellbeing From Baseline To Follow-upsupporting
confidence: 79%
“…Unlike previous studies [6,31,62,66], we did not find higher rates of depression in adolescents with ME/CFS compared with healthy controls, nor an increase in depression over time. However, our findings do support two recent paediatric ME/CFS follow-up studies showing stable depression levels over time [67,68]. Although Loades et al [68] observed consistently higher levels of depression in the paediatric ME/CFS group than healthy controls, baseline ME/CFS depression was found to explain most of the variance in follow-up ME/CFS depression, which appears to suggest stable depression levels across time in paediatric ME/CFS.…”
Section: Trajectories Of Health and Psychological Wellbeing From Baseline To Follow-upsupporting
confidence: 79%
“…This is illustrated by Helen and to some extent David, who continued to be dependent on their parents, who were their carers into adulthood. This combination can further impact managing this complex illness [15]. Another critical factor is if the illness occurs during a transition, e.g., from professional to working mother, when tiredness is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative and qualitative data are limited due to the hard to reach nature of the severely affected CFS/ME population. However, this is slowly changing, and texture is being added to the objective evidence published [15][16][17][18]. In recent years, more qualitative research has been performed with the CFS/ME population.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, I would like to point out an error in the abstract by Ali et al (2019). Contrary to what the abstract claims, fear avoidance was not related to fatigue at follow-up (T2).…”
mentioning
confidence: 88%